Evaluation of DNA damage in lymphocytes of radiology personnel by comet assay. Issue 3 (14th July 2015) - Khisroon, Muhammad; Khan, Ajmal; Naseem, Maryam; Ali, Naheed; Khan, Sardar; Rasheed, Syed Basit
Abstract : Evaluation of DNA damage in lymphocytes of radiology personnel by comet assay: Muhammad Khisroon, et al . Department of Zoology, University of Peshawar, Pakistan Objective: The importance of X‐rays as a diagnostic medical tool cannot be denied. However, continuous exposure to X‐rays can cause DNA damage. This study aimed to use the comet assay technique to investigate the level of DNA damage in lymphocytes due to X‐rays in occupationally exposed personnel. Methods: Blood samples were collected from 74 exposed and 70 control subjects for analysis. A total of 100 randomly captured cells from each slide were examined using an epifluorescent microscope. The comets were analyzed by a visual scoring method according to comet tail length. Results: The results indicated a significant increase ( p <0.05) in DNA damage in X‐rays technicians (129.8 ± 17.2) as compared with the control group (53.0 ± 25.0). A significant increase ( p <0.02) in DNA damage was also observed with an increase in exposure duration of technicians because of their service length. Conclusions: The present study suggests that the exposed radiology personnel should carefully comply with radiation protection procedures such as wearing of lead apron during diagnostic procedures and minimize radiation exposure where possible to avoid potential genotoxic effects due to X‐rays.